Medicago PhosphoProtein Database: a repository for Medicago truncatula phosphoprotein data - Rose, Christopher M.; Venkateshwaran, Muthusubramanian; Grimsrud, Paul A.; Westphall, Michael S.; Sussman, Michael R.; Coon, Joshua J.; Ané, Jean-Michel (Frontiers in Plant Science, 2012)
The ability of legume crops to fix atmospheric nitrogen via a symbiotic association with soil rhizobia makes them an essential component of many agricultural systems. Initiation of this symbiosis requires protein phosphorylation-mediated signaling in response to rhizobial signals named Nod factors. Medicago truncatula (Medicago) is the model system for studying legume biology, making the study of its phosphoproteome essential. Here, we describe the Medicago Phosphoprotein Database (http://phospho.medicago.wisc.edu), a repository built to house phosphoprotein, phosphopeptide, and phosphosite data specific to Medicago. Currently, the Medicago Phosphoprotein Database holds 3,457 unique phosphopeptides that contain 3,404 non-redundant sites of phosphorylation on 829 proteins. Through the web-based interface, users are allowed to browse identified proteins or search for proteins of interest. Furthermore, we allow users to conduct BLAST searches of the database using both peptide sequences and phosphorylation motifs as queries. The data contained within the database are available for download to be investigated at the user’s discretion. The Medicago Phosphoprotein Database will be updated continually with novel phosphoprotein and phosphopeptide identifications, with the intent of constructing an unparalleled compendium of large-scale Medicago phosphorylation data.